Gonadal androgens are associated with decreased type I interferon production by plasmacytoid dendritic cells and increased IgG titres to BNT162b2 following co-vaccination with live attenuated influenza vaccine in adolescents - Sampson, Oliver L.; Jay, Cecilia; Adland, Emily; Csala, Anna; Lim, Nicholas; Ebbrecht, Stella M.; Gilligan, Lorna C.; Taylor, Angela E.; George, Sherley Sherafin; Longet, Stephanie; Jones, Lucy C.; Barnes, Ellie; et al. (Frontiers in Immunology, 2024)
mRNA vaccine technologies introduced following the SARS-CoV-2 pandemic have highlighted the need to better understand the interaction of adjuvants and the early innate immune response. Type I interferons (IFN-I) are an integral part of this early innate response that prime several components of the adaptive immune response. Females are widely reported to respond better than males to tri-and quadri-valent influenza vaccines. Plasmacytoid dendritic cells (pDCs) are the primary cell type responsible for IFN-I production and female pDCs produce more IFN-I than male pDCs since the upstream pattern-recognition receptor TLR7 is encoded by X-chromosome and is biallelically expressed by up to 30% of female immune cells. Additionally, the TLR7 promoter contains several putative androgen response elements and androgens have been reported to suppress pDC IFN-I in-vitro. Unexpectedly, therefore, we recently observed that male adolescents mount stronger antibody responses to the Pfizer BNT162b2 mRNA vaccine than female adolescents, after controlling for natural SARS-CoV-2 infection. We here examined pDC behaviour in this same cohort to determine the impact of IFN-I on anti-spike and anti-receptor-binding domain IgG titres to BNT162b2. Through flow cytometry and Least Absolute Shrinkage and Selection Operator (LASSO) modelling we determined that serum free testosterone was associated with reduced pDC IFN-I but, contrary to the well-described immunosuppressive role for androgens, the most bioactive androgen dihydrotestosterone was associated with increased IgG titres to BNT162b2. Also unexpectedly we observed that co-vaccination with live attenuated influenza vaccine boosted the magnitude of IgG responses to BNT162b2. Together these data support a model where systemic IFN-I increases vaccine-mediated immune responses yet, for vaccines with intracellular stages, modulation of the local IFN-I response may alter antigen longevity and consequently improve vaccine-driven immunity.